P74 Why do patients with copd decline post exacerbation pulmonary rehabilitation?. (15th November 2017) - Mullen, ES; Ward, S; Clinch, L; Chebbout, C; Barley, K; Mitchell-Issitt, C; Gardiner, N; Singh, S
Abstract : Background: Despite the known benefits of post exacerbation Pulmonary Rehabilitation (PR), recruitment can often be difficult. A greater understanding of the reasons why patients hospitalised for an Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) declined the offer of PR is important. Methods: Patients (n=76) admitted to hospital with an AECOPD received a COPD care bundle delivered by COPD specialist nurses. From July to December 2015 patients receiving the care bundle who declined a referral to PR were asked for their reasons for declining. Hospital records were followed up in January 2017 to record admissions and mortality data since the first data collection. Results: Mann Whitney U Tests were carried out to see if there were any differences between the main reasons (Table 1 ) for declining referral and age, MRC, pack years (PY) and/or co-morbidities. Participants who reported that they were not interested in doing PR had a statistically significantly higher PY history (60 vs. 43; p=0.02) compared to patients that chose another reason to decline PR. There was a significant difference between participants MRC scores and the reason they did not want to do PR. Those who did not feel they needed PR reported a lower MRC score range (2–4), compared with the participants in the other options for declining PR; MRC range (3–5);(p=0.005). Patients who gave the reason that felt they did not need PR had a statistically significantly lower number of admissions between their data collection periods (median 2.00 vs. 0.00; p=0.02). Patients who declined PR because they had previously completed the programme compared with those who gave other reasons, had a significantly higher number of hospital admissions during the follow up period (median 4.00 vs. 1.00 p=0.008). There was no statistically significant difference between the number of co-morbidities that patients had and the three main reasons given by patients for declining PR. Conclusions: This data has demonstrated that there are some consistent reasons why people decline PR. Further research is required to identify whether changing how PR is discussed with patients may encourage and help us recruit these types of patients into the PR.